Theoretical Approaches to Empowering SMEs through Technology Adoption: Pathways to Economic Resilience in Nigeria (International Journal of Scientific Research in Science and Technology, 2025)
Small and Medium-sized Enterprises (SMEs) are crucial to Nigeria’s economy, driving employment, innovation, and growth. However, they face significant challenges such as limited technology access, inadequate infrastructure, and regulatory barriers. This concept paper proposes a theoretical framework for empowering Nigerian SMEs through strategic technology adoption to enhance resilience and sustainable development. Grounded in the Technology Acceptance Model (TAM), Diffusion of Innovations (DOI) theory, and the Resource-Based View (RBV), the framework examines factors influencing technology adoption. Key drivers include perceived usefulness, ease of use, cost, and accessibility, while barriers encompass financial constraints and regulatory complexities. The framework highlights government policies, financial incentives, and training programs as critical enablers of technology adoption. Technology adoption enhances SME resilience by improving operational efficiency, reducing costs, and expanding market reach through digital platforms and e-commerce. Policy recommendations include investing in ICT infrastructure, offering financial incentives, providing digital training, and streamlining regulations to foster innovation. Public-private partnerships and business incubators play a vital role in facilitating digital transformation. Robust monitoring and evaluation mechanisms are essential to assess the impact of technology adoption on SME performance. Continuous feedback will ensure that initiatives remain effective and responsive to SME needs. This framework provides a roadmap for leveraging technology to strengthen Nigerian SMEs, fostering economic growth, and positioning them competitively in the digital global economy.